IMPLEMENTATION OF WEB-BASED MARRIAGE MANAGEMENT INFORMATION SYSTEM POLICY IN REALIZING THE IMPROVEMENT OF THE QUALITY OF PUBLIC SERVICES AT THE RELIGIOUS AFFAIRS OFFICE OF BAGUALA SUB-DISTRICT, AMBON CITY - Saniansih, Nia (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research is a qualitative descriptive type study, aiming to analyze and explain the picture of Policy Implementation of marriage management information system at the Office of Religious Affairs Baguala District, Ambon City. The informants in this study numbered 8 people. Data collection techniques used in the form of observation, interviews and documentation as well as analytical techniques used using interactive analysis models from Miles and Huberman, namely using data reduction, data presentation and conclusions. The results of this study show that the implementation of the web-based marriage management information system policy in realizing the improvement of the quality of public services at the Baguala Sub-District Religious Affairs Office has been effective but still not optimal. This can be seen from the indicators of successful policy implementation according to Edward III, namely communication, resources, disposition and bureaucratic structure. The four indicators are influenced by supporting and inhibiting factors that affect the implementation of the marriage management information system in KUA, Baguala District, Ambon City.